Effects of temperature, salt and ascorbic acid on the structure and yellow discoloration of cuttlefish fillet during cool storage - Tran , Hoang De; Tran , Thanh Truc (Journal of Technical Education Science, 2016)
An observation and treatment method of texture and color modification of prefreezing cuttlefish fillet are performed based on the control of storage temperature, NaCl, ascorbic acid concentration to prevent and reduce fillet’s discoloration on cuttlefish fillet. In this research, the physical result effecting on cuttlefish fillet discoloration is storage temperature. The chemical aspects strongly impacting on coloration and keeping water ability are NaCl solution, antioxidant - ascorbic acid. Soaking cuttlefish fillet in 2 ÷ 4oC with 3% NaCl and 0,2% ascorbic acid solution helps restrict the yellow discoloration and improve water holding capacity and the structure of cuttlefish fillet.